NEW EVIDENCES FOR TRIASSIC MORB MAGMATISM IN THE NORTHERN MIRDITA ZONE OPHIOLITES (ALBANIA) - Bortolotti, Valerio; Chiari, Marco; Kodra, Alaudin; Marcucci, Marta; Mustafa, Faruk; Principi, Gianfranco; Saccani, Emilio (Ofioliti, 2004)
A succession of mid-ocean ridge basalts (linked at their base to serpentinite slivers) with intercalations of chert levels of Middle and Late Triassic, as well as Early and Middle Jurassic ages have recently been found in the Argolis Peninsula, Greece (Bortolotti et al., 2001; 2002a; 2003; Saccani et al., 2004a). This succession shows the same lithostratigraphic and tectonic setting of the Triassic basalts of the “Volcano- sedimentary Formation” at the top of the “Rubik Complex” of the Mirdita Ophiolitic Nappe in Albania (Bortolotti et al., 1996; 2002b; 2004). Moreover, Argolis and Mirdita ophiolites belongs to the same ophiolitic belt, which extends from Mirdita to Pindos, Vourinos, Othrys and Argolis.The “Volcano-sedimentary Formation” was previously interpreted by Kodra et al. (1993) as an Upper Jurassic sequence, which “precède de peu ou accompagne le début de l’ouverture (océanisation) proprement dite du domaine ophiolitique de Mirdita” (p. 66). Bortolotti et al. (1996) confirmed this interpretation (“the sequence can be interpreted as a product of syn-rift, subalkaline magmatism associated with thinning of the continental margin during the Middle Triassic”; p. 5). Thus, on the bases of the radiolarian stratigraphy, this sequence has been retro-dated to the Middle and Late Triassic times (Bortolotti et al., 1996; 2002b; Chiari et al., 1996).The aim of this paper is to assess the petrology and tectono-magmatic significance, with respect to the age of formation, of basalts from this complex in the northern Albania Mirdita zone, to provide new data for a more detailed reconstruction of the Triassic tectono-magmatic events related to the formation of the Tethys oceanic basin in the Dinaric- Hellenic area.